L is for lawless [large type] - Grafton, Sue (Grafton, Sue. Kinsey Millhone mysteries., 2015)
PI Kinsey Millhone of California goes looking for the loot of a $500,000 robbery, an assignment filled with danger as one of the robbers is a psychopath.